Sosialisasi Kecerdasan dalam Memaknai Pesan Media Era Digital: Fakta Versus Hoax di Pesantren Nurul Falah Meulaboh - Desi Maulida; Irma Juraida; Arfriani Maifizar; Rahmah Husna Yana (Universitas Teuku Umar, 2019)
Education about the use of media especially digital media is now important to be given to all levels of society, especially the younger generation, so that this socialization is aimed at students at the Nurul Falah Islamic Boarding School Dayah Inti Meulaboh. The method of socialization used was the presentation of theories about social media including how to distinguish between facts and hoax. The socialization took place interactively, there was a discussion room so as to facilitate the speaker in achieving the objectives of the socialization.. The results of socialization show that initially the students did not really understand related to how to filter information to distinguish hoax and facts. That is because, they are less intense using handphone, so that students can easily trust information obtained from the internet, especially social media. With this socialization, students have been theoretically equipped about how to filter information and distinguish between hoax and facts, and are able to stimulate students to be more observant and critical in responding to information.